The Application Of Project Based Learning Method To Decreasing English Department Sudents’ Academic Procrastination - Rini Kesuma Siregar; Nursaima Harahap; Lisa Fitri Meidiapa (English Department, University of Riau Kepulauan, Batam,Indonesia, 2018)
This study aims to see the reduction of procrastination of the student academic by using project based learning / task leaning. The method used is classroom action research. Data collection was taken from 28 students, giving them a questionnaire to see the reduction of procrastination of the student by using project based learning. The results of the analysis showed that before the action was taken, student academic procrastination was still very high, but after action could be seen that there was a reduction in the academic procrastination of students in the first cycle 27.01% and in the second cycle 38.47%, the results obtained in the second cycle showed that the expected category is more than 30%, meaning that it has reached more than the target.